Construction of Participatory Teaching Quality Assurance System - Qin, Chen; Fancai, Zeng; Mei, Feng; Chun yu, Wang (American Journal of Human Ecology, 2013)
<!--[if gte mso 9]> <![endif]--> Since the 1980s，as the awakening of subjectivity and the widely implementation of subjectivity education, university stakeholders as subject participation has becomes the core of improving the education quality in modern society, teaching Quality Assurance (QA) System. However, by contrast, the concepts such as university stakeholders don’t have the abilities to participate in university management, still prevail in the field of QA System in university. Participatory management advocates that university stakeholders participate in quality control and management. Introduced the establishment of teaching QA system one of the core contents in meticulous management -- participation of all members through the entire process by overall conversion in order to explore the construction of teaching QA system designed by all college stakeholders who also take part in the system, to reform education and teaching in the interdependent world, to strengthen the construction of the QA system. Participation is certain to be fruitful in cultivating talents with assurance. Through the establishment of the participatory teaching QA system, the college personnel training has been enhanced with significant economic and social benefits. According to the statistics from National Examination Center, in recent years, the pass rate of qualification examination by our clinical majors, stomatology students, preventive medicine majors, and nurse major graduates is several points percent higher than national average pass rate and the one-time pass rate of National Judicial Examination for a certificate by our law (medical law) major students is much higher than the national average pass rate. Construction of participatory teaching QA system is a useful tool to form a long-term mechanism for participatory teaching QA system and to achieve the maximized operation efficiency of educational resources and continuous improvement of the teaching quality. <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; text-align:justify; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin;} --> <!--[endif] -->